Video Laryngoscopes: A Boon for Parapharyngeal Tumors of Childhood - Man Bhavan Mahajan; Mamta sharma; Rupali Mahajan (Archives of Anesthesia and Critical Care, 2023)
Parapharyngeal tumors often distort the airway anatomy leading to obstruction and hinderance for intubation thus posing a challenge for the anesthetist at securing airway with least damage to the nearby structures. We present our experience through a series of 5 such cases in children managed successfully using video laryngoscope. Working in places where availability of advanced airway equipment such as pediatric size fiberoptic is unavailable, a video laryngoscope can help to appropriately assess the airway and prevent disastrous outcomes.